2013
DOI: 10.4269/ajtmh.12-0525
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Selection of Plasmodium falciparum Chloroquine Resistance Transporter Gene and Multidrug Resistance Gene-1 Haplotypes Associated with Past Chloroquine and Present Artemether-Lumefantrine Use in Inhambane District, Southern Mozambique

Abstract: Abstract. Chloroquine (CQ) use in Mozambique was stopped in 2002 and artemether-lumefantrine (AL) was implemented in 2008. In light of no use of CQ and extensive use of AL, we determined the frequency of molecular markers of Plasmodium falciparum drug resistance/tolerance to CQ and AL in persons living in Linga-Linga, an isolated peninsula and in Furvela village, which is located 8 km inland. The P. falciparum chloroquine resistance transporter gene CVMNK wild type increased in frequency from 43.9% in 2009 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
50
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 38 publications
11
50
1
1
Order By: Relevance
“…pfcrt K76 and pfmdr1 N86 are selected for after treatment with AL and are linked to reduced lumefantrine susceptibility (7)(8)(9)14). The pfmdr1 86 ϩ 184 ϩ 1246 NFD haplotype has been selected for by AL (7,15,16). Furthermore, an increased pfmdr1 copy number has been linked to reduced susceptibility to artemisinin derivatives, lumefantrine, piperaquine, and mefloquine and to artesunate plus mefloquine treatment failure (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…pfcrt K76 and pfmdr1 N86 are selected for after treatment with AL and are linked to reduced lumefantrine susceptibility (7)(8)(9)14). The pfmdr1 86 ϩ 184 ϩ 1246 NFD haplotype has been selected for by AL (7,15,16). Furthermore, an increased pfmdr1 copy number has been linked to reduced susceptibility to artemisinin derivatives, lumefantrine, piperaquine, and mefloquine and to artesunate plus mefloquine treatment failure (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…An explanation for the absence of this mutant allele could be attributed to the widespread use of AL as a second-line treatment within ACTs; possibly selecting for the pfmdr1 N86 wild-type allele. In this context, several studies suggested that AL contributes to the selection of pfmdr1 N86 wild-type allele among parasite isolates in Africa (Happi et al, 2009;Kamugisha et al, 2012b;Malmberg et al, 2013;Raman et al, 2011;Sisowath et al, 2005;Thomsen et al, 2011Thomsen et al, , 2013. Pooled analysis of 31 clinical efficacy studies identified pfmdr1 N86 as an independent predictor of recrudescence in patients treated with AL and recommended its routine detection for monitoring resistance to the combination (Venkatesan et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Several previous reports showed a significant pfcrt 76T decline after CQ withdrawal in Malawi (Kublin et al, 2003;Laufer et al, 2006), Tanzania Mozambique (Thomsen et al, 2013) and Ethiopia (Mekonnen et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…In Kenya, when CQ use in malaria treatment was stopped from 1993 to 2006, CQ susceptibility rose from 5% to 40%. Similarly, in Mozambique, CQ susceptibility rose from 5% to 80% within 5 years of policy change, 43 while in Malawi there was 100% CQ susceptibility recorded in 13 years following the change in malaria treatment policy. 15,36 Thus, there is evidence that the change in malaria treatment policy has had an effect on reversal of CQ susceptibility in different African countries.…”
Section: Discussionmentioning
confidence: 99%